2008
DOI: 10.1002/jcp.21376
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori heat shock protein B (HspB) localizes in vivo in the gastric mucosa and MALT lymphoma

Abstract: Heat shock protein B (HspB) is one of the dominant proteins recognized by most Helicobacter pylori-infected persons and is being considered as potential candidates for subunit vaccines. In the present study we describe the generation of an antibody against HspB and its use in immunohistochemical assays on gastric biopsies. We have demonstrated that our rabbit polyclonal antibody against HspB did not recognize any protein in lysates from a lung human epithelial cell (H1299) line and did not cross-react with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…As for the relationship between MALT lymphoma and H. pylori factors, the presence of anti‐CagA IgG antibodies were confirmed to be a risk factor for lymphoid follicle development in patients with gastritis [48]. Immunohistochemistry analyses showed that cytoplasmic heat shock protein B (HspB) immunostaining was observed in groups of neoplastic cells of MALT lymphoma [49]. HspB is one of the dominant proteins of H. pylori and is being considered as a potential candidate for subunit vaccines, and the data suggest a possible involvement of HspB in the pathogenesis of H. pylori ‐related development of MALT lymphoma.…”
Section: Gastric Carcinomamentioning
confidence: 99%
“…As for the relationship between MALT lymphoma and H. pylori factors, the presence of anti‐CagA IgG antibodies were confirmed to be a risk factor for lymphoid follicle development in patients with gastritis [48]. Immunohistochemistry analyses showed that cytoplasmic heat shock protein B (HspB) immunostaining was observed in groups of neoplastic cells of MALT lymphoma [49]. HspB is one of the dominant proteins of H. pylori and is being considered as a potential candidate for subunit vaccines, and the data suggest a possible involvement of HspB in the pathogenesis of H. pylori ‐related development of MALT lymphoma.…”
Section: Gastric Carcinomamentioning
confidence: 99%
“… 34 Heat shock proteins are essential stress-induced molecular chaperones that facilitate protein folding and remodeling critical for virtually all main cellular processes, 35 with evidence of intracellular localization in the cytosol of infected gastric mucosa cells. 36 Proteomic studies showed that H. pylori cysteine-rich proteins can interact directly and indirectly in complex formation with human heat shock protein members and other intracellular proteins important in the response to viral and bacterial infection. 37 HspA by itself is a strong promoter of an inflammatory-type cytokine response via the Toll-like receptor-4-mediated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, H. pylori ‐infected cells are impeded to activate the antioxidant response (Buommino et al, ). Moreover, co‐expression of CagA and HspB in AGS cells is able to induce cell cycle proliferation through an increase of rate of transit between the S/G2‐M phase of the cell cycle associated with a specific increase in cyclin D3 and Retinoblastoma gene product, Rb, in its phosphorylated form (De Luca et al, 2003, 2008). Hence, HspB deserves great attention since it has been demonstrated that its activity increases the risk of gastric carcinoma (Iaquinto et al, ).…”
Section: Molecular Mechanism Of H Pylori Pathogenesismentioning
confidence: 99%